"Too little, too late?" Will inhibitors of the hepatitis C virus p7 ion channel ever be used in the clinic?. (November 2014) - Griffin, Stephen
Hepatitis C virus (HCV) p7 is a virus-coded ion channel, or 'viroporin'. p7 is an essential HCV protein, promoting infectious virion production, and this process can be blocked by prototypic p7 inhibitors. However, prototype potency is weak and effects in clinical trials are unsatisfactory. Nevertheless, recent structural studies render p7 amenable to modern drug discovery, with studies supporting that effective drug-like molecules should be achievable. However, burgeoning HCV therapies clear infection in the majority of treated patients. This perspective summarizes current understanding of p7 channel function and structure, pertaining to the development of improved p7 inhibitors. We ask, 'is this too little, too late', or could p7 inhibitors play a role in the long-term management of HCV disease?